Legal Children Protection as Victim of Psychological Violence in Surakarta - Oktaviary, Adinda Rizky; Kurnianingsih, Marisa; Andi Intan Purnamasari (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This study aims to reveal how Surakarta government faces legal protection. Also, constraints in providing fulfillment of the rights of child victims of psychological violence committed in the family environment. This study uses an empirical juridical method interview and examine the legal provisions that apply in society. It focuses on violence against children committed by their parents, which has an impact on the child's psychology with valid data sourced from the authorities. Although violence against children is a violation of human rights, without realizing it, there are still many people who are willing to commit acts of psychological violence against children. It is because the child is unlikely to rebel when they receive improper treatment from adults, including within the scope of their own family, even though this treatment will have an impact on the child's psychology in the future. The results revealed that illustrate the psychological violence is only considered an internal family problem, and not many people realize it as an act of violence. Surakarta government has actually made efforts to prevent and reduce the number of violence against children, such as by providing an understanding of the importance of giving good parenting, being more able to control emotions, and being sensitive to the conditions and needs of children. This study concludes that the Surakarta government, through DP3AP2KB, has made various efforts to deal with cases of violence that can have an impact on children's psychology. However, these efforts are not fully supported by the public due to the lack of understanding and awareness of the dangers of violence against children, so the number of child abuse in Surakarta has not been a significant change.